2019
DOI: 10.24310/espsiescpsi.v12i2.10065
|View full text |Cite
|
Sign up to set email alerts
|

Adicción al móvil e internet en adolescentes y su relación con problemas psicopatológicos y variables protectoras

Abstract: Se analizó la relación entre psicopatología y abuso del móvil e internet en adolescentes, además, se analizaron si ciertas variables protectoras de psicopatología protegen también del abuso del móvil e internet y se calcularon los puntos de corte dos cuestionarios que miden el abuso de estas tecnologías. Se empleó una muestra de 269 adolescentes entre 12 y 18 años (124 chicos y 145 chicas) y se usaron los cuestionarios YSR para medir psicopatología, CERI abuso de internet y CERM abuso del móvil. Los resultados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
0
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
2
0
0
4
Order By: Relevance
“…Moreover, symptoms of anxiety/depression ( OR = 1.125), dissocial behavior ( OR = 1.256) and inadequate performance in subjects related to Social Sciences ( OR = 6.988), are more probability with a greater number of attention deficit symptoms. These results coincide with those from other research, that poor academic performance, psychopathological problems, somatizations, sleep disorders, and behaviors related to poor self-control, such as internet abuse, video games or alcohol ( Martin, 2014 ; Mhalla et al, 2018 ; Vicente-Escudero et al, 2019 ), are factors significantly linked to the appearance of ADHD symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, symptoms of anxiety/depression ( OR = 1.125), dissocial behavior ( OR = 1.256) and inadequate performance in subjects related to Social Sciences ( OR = 6.988), are more probability with a greater number of attention deficit symptoms. These results coincide with those from other research, that poor academic performance, psychopathological problems, somatizations, sleep disorders, and behaviors related to poor self-control, such as internet abuse, video games or alcohol ( Martin, 2014 ; Mhalla et al, 2018 ; Vicente-Escudero et al, 2019 ), are factors significantly linked to the appearance of ADHD symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, there is concordance between our ADHD scales and externalizing, attention, and self-control problems. These are common in studies examining ADHD and its correlations, and these same relationships are found in other studies ( Kuja-Halkola et al, 2015 ; Vicente-Escudero et al, 2019 ), indicating that adapted ADHD scales are adequate to measure this problem.…”
Section: Discussionsupporting
confidence: 71%
“…El smartphone, o teléfono móvil inteligente, es el elemento más usado por los jóvenes y adolescentes. Se estima que el 99 % de la población entre los 16 y los 20 años lo utiliza diariamente (Bernal Ruiz et al, 2017;Vicente-Escudero et al, 2019), permitiéndoles conectarse con sus iguales a través de las redes sociales y de las aplicaciones (app) de mensajería instantánea (Garrote-Rojas et al, 2018;Marín-Díaz et al, 2019;Romero Rodríguez y Aznar Díaz, 2019). Otra de las fuentes de conflicto derivadas del uso de los smartphones son las redes sociales y WhatsApp (Castellanos Rosas et al, 2020;Conde Miranda, 2018;Hilt, 2019;Ruiz de Miguel, 2016;Sosa et al, 2019).…”
Section: Introductionunclassified
“…Recientes estudios revelan que casi el 25% de los encuestados eran adictos al móvil (26,27). Se han encontrado asociación entre la adicción al smartphone con síntomas de depresión, ansiedad, fatiga mental, mala calidad del sueño (6, 28, 29); además con problemas físicos, como visión borrosa, dolor en las muñecas o en el cuello (30) y con problemas mentales o de comportamiento (31).…”
Section: Introductionunclassified